DAMPAK MODAL SOSIAL TERHADAP KEPUTUSAN PENDANAAN DALAM MENGELOLA TEKANAN KEUANGAN (Studi Pada UMK Batik di Kota Semarang) - Suryakusuma K H; Siti Puryandani (JURNAL STIE SEMARANG, 2018)
The purpose aim how financial performance in a business situation have financial distress and how entrepreneurs react to environmental changes and take advantage of the social capital for sustainability.This study will investigate the social capital, the financial decision and financial distress. The research objects are SME Batik Semarang thats tenant by goverment bank in Semarang. The SME Batik have operational during 2017 and total questionare are collecting 36 SME Batik.The result argue that social capital have impact to the financing decision and financing decision eventually influences financial distress.